English errors and Chinese learners - Abdul Rashid Mohamed; Goh, Li Lian; Eliza, Wan Rose (Sunway University College, 2004)
This paper examines the errors committed by second language learners in English essay writing based on eight selected grammatical items and makes recommendations to improve English writing skills in Malaysia. While errors were once regarded with contempt and looked upon as something to be avoided at all cost, they are now perceived to represent stages of language acquisition. The objectives of this paper are to identify and classify comprehensible and incomprehensible errors committed by the respondents, and attempt to explain the probable causes of such errors. Analyses of data revealed that most of the errors committed by the respondents were comprehensible ones. With reference to the selected grammatical items, the analysis established that respondents faced particular difficulty in the use of verbs, prepositions and spellings. The research further showed that the errors committed by the respondents were due to over-generalization and simplification. The paper thus recommends the incorporation of explicit grammar instructions in the teaching of English as a second language in order to improve grammatical competence in English writing.